Operations management : an international perspective - Barnes, David (Thomson, 2008)
This fascinating new core textbook, authored by a highly respected academic with over a decade of industry experience, takes a global and strategic approach to the important topic of operations management (OM). Integrating contemporary and traditional theories the text covers everything a student needs to understand the reality of operations in the modern world and combines the latest cutting-edge thinking with innovative learning features. Written in a concise and engaging style and based on up-to-date research in the field, the book provides a range of international case studies and examples that help students to apply theoretical knowledge to real-world practice